Mitochondria are positioned at dendritic branch induction sites, a process requiring rhotekin2 and syndapin I - Jessica Tröger; Regina Dahlhaus; Anne Bayrhammer; Dennis Koch; Michael M. Kessels; Britta Qualmann (Nature Communications)
Abstract Proper neuronal development, function and survival critically rely on mitochondrial functions. Yet, how developing neurons ensure spatiotemporal distribution of mitochondria during expansion of their dendritic arbor remained unclear. We demonstrate the existence of effective mitochondrial positioning and tethering mechanisms during dendritic arborization. We identify rhotekin2 as outer mitochondrial membrane-associated protein that tethers mitochondria to dendritic branch induction sites. Rhotekin2-deficient neurons failed to correctly position mitochondria at these sites and also lacked the reduction in mitochondrial dynamics observed at wild-type nascent dendritic branch sites. Rhotekin2 hereby serves as important anchor for the plasma membrane-binding and membrane curvature-inducing F-BAR protein syndapin I (PACSIN1). Consistently, syndapin I loss-of-function phenocopied the rhotekin2 loss-of-function phenotype in mitochondrial positioning at dendritic branch induction sites. The finding that rhotekin2 deficiency impaired dendritic branch induction and that a syndapin binding-deficient rhotekin2 mutant failed to rescue this phenotype highlighted the physiological importance of rhotekin2 functions for neuronal network formation.